Dracula - Stoker, Bram, 1847-1912 ([Boston, Mass] : Thomson Heinle, 2007)
Jonathan Harker is sent to see a client of his company in a distant part of Europe. The castle is deserted and the Count is a very strange host. But little does young Jonathan suspect that he and the people closest to him are about to be put into the worst danger and the most grusome terror that anyone can imagine! Now they must track and destroy Dracula before he finds and destorys each of them
Title from container
Keywords: Dracula, Count (Fictitious character); Vampires -- Fiction; Transylvania (Romania) -- Fiction